An Entrepreneur perspective to the Singapore Body Wellness Industry - LIM, CHEE HAN (2009)
Executive Summary Singapore economic started off with global trade and this approach saw its weakness in this credit crunch. The GDP has fallen sharply with expected lower trade. Since last year, the government has been encouraging entrepreneurship through various funding especially in green energy and life science industry. There are also funding in helping bank to release loan to companies through sharing loan default risk. Entrepreneurs are stubborn people whom held their belief close to themselves and strive to overcome difficulties. They walk the lonely and less travelled path which most people (e.g. salary employees) avoid due to the uncertainly. One of the neglected industries is the body wellness which is a form of preventive healthcare. This is done through de-stressing which prevent “body toxic” from accumulating. The body wellness industry in Singapore has resembled a “perfect market” environment with many small players popping up in neighborhood estate in various shape and size. Their obsession in generating profit for survival resulted in poor, unprofessional or immoral services. The lean operation has enticed price sensitive consumers but diminish this profession. The price cutting strategy is easily copied by others and the lower profit margin result in businesses using inferior products which does not achieve “body wellness”. How can we compete in such a chaos environment? This paper aims to find that answer using Creative Problem Solving Model (CPSM). The model uses various thinking quadrants (HBDI) or mindset (e.g. Artist and Judge) to obtain an unbiased and optimum solution. It forces the user to identify the real problem before solving it. The paper is broken into 3 Sections • Section A gives an overview of the entrepreneurship in Singapore. • Section B provides the literature study made on HBDI and CPSM • Section C will provide a real case study based on the author experience The focus is on the initial startup as we find that this stage is important and is often neglected. We hope the reader will find the discussion here useful and inspiration in their entrepreneurship path. Enjoy the reading.